2020
DOI: 10.9778/cmajo.20200100
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing early Canadian federal, provincial, territorial and municipal nonpharmaceutical interventions in response to COVID-19: a descriptive analysis

Abstract: Background: Nonpharmaceutical interventions (NPIs) are the primary tools to mitigate early spread of the coronavirus disease 2019 (COVID-19) pandemic; however, such policies are implemented variably at the federal, provincial or territorial, and municipal levels without centralized documentation. We describe the development of the comprehensive open Canadian Non-Pharmaceutical Intervention (CAN-NPI) data set, which identifies and classifies all NPIs implemented in regions across Canada in response to COVID-19,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 13 publications
4
40
0
Order By: Relevance
“…Similar to our scoping review, the results of a descriptive study on non-pharmaceutical interventions (NPIs) implemented in Canada reported that jurisdictions issued many of their PH measures after 11 March 2020. 6 This date coincides with the WHO's pandemic declaration. The authors also observed some consistency with Europe and Asia in the order of NPI implementation, and less variation across Canada in the implementation of NPIs compared with the USA.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Similar to our scoping review, the results of a descriptive study on non-pharmaceutical interventions (NPIs) implemented in Canada reported that jurisdictions issued many of their PH measures after 11 March 2020. 6 This date coincides with the WHO's pandemic declaration. The authors also observed some consistency with Europe and Asia in the order of NPI implementation, and less variation across Canada in the implementation of NPIs compared with the USA.…”
Section: Discussionmentioning
confidence: 61%
“…The authors also observed some consistency with Europe and Asia in the order of NPI implementation, and less variation across Canada in the implementation of NPIs compared with the USA. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second provides information about country/countries of study and references. Category Country and references Implementation of NPIs Government response trackers: Canada [384] , 195 countries [385] , 180 countries [348] , 56 countries [42] ; Universities response in USA [386] Mobility Australia, Brazil, China, Ghana, India, Iran, Italy, Norway, South Africa, USA [387] ; Italy [40] Contacts Belgium, China, Finland, France, Germany, Italy, Hong Kong, Luxembourg, Netherlands, Poland, Peru, Russia, South Africa, UK, Vietnam, Zambia, Zimbabwe [41] …”
Section: Datasetsmentioning
confidence: 99%
“…Authors in Ref [384] apply the taxonomy defined by the Oxford COVID-19 Government Response Tracker to the case of Canada. The data, together with many other relevant datasets from Canada and other countries, can be found here: https://howsmyflattening.ca/#/data .…”
Section: Datasetsmentioning
confidence: 99%